Are New Tigers supplanting Old Mammoths in China’s banking system? Evidence from a sample of city commercial banks - Ferri, Giovanni (Journal of Banking & Finance, 2009)
“New Tigers” (including city commercial banks) outperform state-owned commercial banks burdened with non-performing loans from unprofitable state-owned enterprises. We study whether this is solely due to superior corporate governance (multiple shareholders versus total government ownership) or also to the favorable environment (the New Tigers target affluent China, while state-owned commercial banks operate nationwide). Using a field survey on 20 city commercial banks from three provinces at different levels of economic development, we find better performance at those in the East and worse performance at those controlled by state-owned enterprises. Geography and policy do matter, and reform of state-owned commercial banks is necessary to bring better banking to China.